Eating behavior and body image perception: an epidemiological study on Italian Adolescents - Pruneti, C.; Fontana, F.; Bicchieri, L. (Acta Biomedica Atenei Parmensis, 2004)
In order to identify some of the psychological-environmental factors behind an unbalanced diet or incorrect eating habits which may be connected to the onset of eating-behavior disorders. A sample of 4550 teenagers (2221 males and 2329 females) aged between 12,3 and 18,9 years (mean age = 14.49 ± 3.8), was consecutively recruited taken from several secondary schools and high schools. The Pisa Survey for Eating Disorders (PSQ), a questionnaire aimed at evaluating both eating habits and self-perception of body image, was administered. Answers given to some items have highlighted a recurrence of cognitive distortions, an excessively rigid self-perception of body image as well as frequent, often daily, dysfunctional eating habits. The PSED questionnaire has proved itself to be a useful and easy-to-use tool. It helps to reveal maladjusted behavior and to evaluate probable risk factors connected with the development of eating and emotional disorders.